Development of a Computerized Maintenance Management System (CMMS) : A Case Study of Latex Gloves Manufacturer - อธิกุลรัตน์, กิตตชัย; นาคพรหม, ลลิดา; ม่วงขาว, กฤษดา (RMUTL Engineering Journal, 2019)
The objective of this research is to develop and improve the maintenance system of latex gloves manufacturing.The computerized maintenance management system has been developed in Python to collect and manage the maintenance information in the database which consists of the employee profile, the machinery and the spare parts. In addition, the database program can help search the maintenance records more quickly and conveniently. Based on the results of this study, it was found that the maintenance time of the new system decreased from the existing system 1,140 seconds to 64 seconds, or reduced by 94.39%, which leads to higher efficiency of maintenance management system